Tinjauan Kriminologis: Korban Teror Pasca-Demonstrasi di Gedung DPRD Kota Bandung (Studi Kasus Demonstrasi Mahasiswa Di Bandung) - Sulthanah, Izdihar; Gresia, Keisha Putri; Syahbaningsih, Sielvaniyah (INDO PUBLISHING, 2025)
This study examines the phenomenon of post-demonstration terror among students around the Bandung City DPRD Building from a criminological perspective, focusing on the impact of post-demonstration victims and the causes experienced by the victims. Using a qualitative approach through in-depth interviews with 7 victims (students). The study identified three main patterns: (1) psychological terror through verbal and non-verbal threats, (2) the inability of authorities to separate provocative groups from peaceful demonstrators, and (3) the lack of victims' access to psychosocial services. These terror findings indicate that post-demonstration terror is a consequence of the weakness of the law enforcement system in security supervision and inequality in access to justice for vulnerable groups. The contribution of this study lies in mapping the vulnerability of non-demonstrator victims which is rarely discussed in public security studies in Indonesia.